2021
DOI: 10.3390/ijerph18041496
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Feeding Practices and Food Literacy in Parents with Young Children from Disadvantaged Areas

Abstract: Early childhood provides an opportunity to optimize growth and development and parents play a fundamental role in forming healthy eating habits in their children. A healthy diet improves quality of life and wellbeing and reduces the risk of chronic disease. The aim of this research was to explore parents’ experiences of feeding 0–5-year-old children and food literacy behaviors. This qualitative study employed a general inductive inquiry approach. Participants were recruited through community-based parenting or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…One recent study showed that most Greek parents were nutritionally literate, which was shown to positively influence the feeding patterns of their children (22). Consistent with the present study's findings, one study showed that parents experienced various unpleasant emotions when feeding their children, including anxiety, difficulty, and concern (23). Furthermore, several challenges were encountered by parents when trying to share food literacy skills with their children, including time pressure, safety concerns, lack of interest from children, and conflict between siblings (24).…”
Section: Parental Food Literacy and Potential Intervention Programssupporting
confidence: 87%
“…One recent study showed that most Greek parents were nutritionally literate, which was shown to positively influence the feeding patterns of their children (22). Consistent with the present study's findings, one study showed that parents experienced various unpleasant emotions when feeding their children, including anxiety, difficulty, and concern (23). Furthermore, several challenges were encountered by parents when trying to share food literacy skills with their children, including time pressure, safety concerns, lack of interest from children, and conflict between siblings (24).…”
Section: Parental Food Literacy and Potential Intervention Programssupporting
confidence: 87%
“…Addressing these interconnected factors requires comprehensive interventions. Strategies should focus on improving access to nutritious food, promoting optimal feeding practices, providing early childhood education programmes that foster cognitive and socio-emotional development, and creating supportive environments that stimulate learning and positive social interactions ( 35 , 36 ) . By addressing these factors, it is possible to improve the ECDI outcomes of children with nutritional disorders and promote their overall optimal development.…”
Section: Discussionmentioning
confidence: 99%
“…The program's development was shaped by formative research conducted to assess the feeding experiences and challenges faced by the parents' of 0 to 5 year old children in providing them with a healthy diet. Formative research included eight focus groups with parents 6 ( n = 67); semi‐structured interviews with stakeholders ( n = 14) from parenting organisations in WA; and consultation via a stakeholder forum ( n = 31) with professionals in child health, nutrition, health promotion and community organisations that work with families.…”
Section: Methodsmentioning
confidence: 99%
“…5 Research shows that parents are motivated to provide nutritious foods; however, feeding children under 5 years of age presents many challenges, including a lack of time, multiple and conflicting sources of information, children's own food preferences, cost and food insecurity. 6,7 Children who are perceived as fussy eaters create anxiety, frustration and stress for parents, which affects parents' feeding decisions. 3,6 The term 'positive parenting feeding practices' will be used throughout this paper to describe the combined evidence-based feeding strategies encompassing responsive feeding practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation